2014
DOI: 10.1140/epjb/e2013-40949-5
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and spectra of CuO

Abstract: We report the electronic structure of monoclinic CuO as obtained from first principles calculations utilizing density functional theory plus effective Coulomb interaction (DFT + U) method. In contrast to standard DFT calculations taking into account electronic correlations in DFT + U gave antiferromagnetic insulator with energy gap and magnetic moment values in good agreement with experimental data. The electronic states around the Fermi level are formed by partially filled Cu 3d x 2 −y 2 orbitals with signifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 67 publications
(151 reference statements)
9
52
0
Order By: Relevance
“…41 However, calculations accounting for SOC found the band gap to start at the Fermi level and be 1.2 eV in magnitude. 45 This value agrees better with experimental values and supports the claim that SOC is an important factor for this class of compounds.…”
Section: ■ Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…41 However, calculations accounting for SOC found the band gap to start at the Fermi level and be 1.2 eV in magnitude. 45 This value agrees better with experimental values and supports the claim that SOC is an important factor for this class of compounds.…”
Section: ■ Introductionsupporting
confidence: 88%
“…In addition to the strong Coulombic interactions mentioned above, a recent investigation, focused on elucidating the electronic structure of CuO, found that spin−orbit coupling (SOC) also plays an important role. 45 Without SOC, the valence band ends 1.17 eV above the Fermi level, after which there is a small gap of 0.49 eV, consistent with prior theoretical estimates. 41 However, calculations accounting for SOC found the band gap to start at the Fermi level and be 1.2 eV in magnitude.…”
Section: ■ Introductionsupporting
confidence: 87%
“…Recently, Wang et al predicted that the indirect band gap of Cu 4 O 3 is 1.59 eV [4]. As for CuO, the type of band gap of CuO remains controversial; in some studies its band gap is suggested to be direct [16,17,18], but it is considered that its band gap is indirect in other studies [1,19,20], and its accurate band gap value is still a greater challenge for electronic structure calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Although CuO has received wide attention since the discovery of high temperature cuprate superconductors, its electronic structure has not been fully settled. The onset of direct-allowed absorption has been determined at 1.57 eV at low temperature [15], but the type of band gap (direct [28][29][30] or indirect [12,16,21,31]) remains controversial. The correlated nature of CuO presents a greater challenge for electronic structure calculations.…”
mentioning
confidence: 99%